E Pluribus … Pluribus? Politics, Polarization, and Prospects for Covenantal Pluralism in the United States Today - Olson, Laura R. (The review of faith & international affairs, 2025)
This article asks whether there is a path forward in the United States for what scholars have termed "covenantal pluralism." I combine insights from a variety of literatures with survey data and other resources to make the case that, notwithstanding some positive precedents, practices, and potentialities, covenantal pluralism faces an uphill climb in the United States today. After discussing broad trends in religious demography and the social implications of those trends, I proceed to assess contemporary American conditions per three standard constitutive dimensions of covenantal pluralism: freedom of religion and belief, cross-cultural religious literacy, and virtues that support nonrelativistic pluralism.